Studi Kasus: Asuhan Keperawatan Pada Pasien Dengan Mioma Uteri Disertai Diabetes Melitus - Anggi Anggraini; Merida Simanjuntak (AKPER Pasar Rebo, 2022)
Abstract Background: Uterine myoma is a benign neoplasm derived from uterine muscles and connective tissue, found in women aged 35-45 years and nulipara or less fertile. One of the risk factors causing uterine myoma is diabetes mellitus. Global Health Data (2019), patients with uterine myoma in the world reached 226 million cases while in Indonesia 3.7 million cases. Based on data from dr. Chasbullah Abdulmadjid hospital, there were 26 uterine myoma patients in 2020 while in 2021 there were 66 patients. Objective: this study aims to determine nursing care in patients with uterine myoma accompanied by diabetes mellitus. Method: this study used a descriptive method with an approach through the management of nursing care in Mrs. I patients with uterine myoma accompanied by diabetes mellitus. Results: this study was conducted in the Jasmine room of dr. Chasbullah Abdulmadjid Hospital, Bekasi City in March 2022 for two days. Data collection was carried out through observation techniques and interviews. Based on the study, several nursing problems were found, namely the risk of bleeding, acute pain, instability of blood glucose levels and the risk of infection. Conclusion: of the four diagnoses established, only one of them was resolved. Keywords : nursing care, diabetes mellitus, uterine myoma